STRATEGI PENGEMBANGAN WISATA BENSAMAR KAMPONG TUHA DI LOA IPUH DARAT KECAMATAN TENGGARONG - TABLIK, MUHAMMAD; Luthman, Awang Yacoub; Putri, Eva Noorhya Akhmar Ramadhan (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2024)
This research aims to formulate the right strategy in developing tourism in Bensamar Kampong Tuha by considering five key variables namely environmental protection, revitalization of history and culture, local wisdom, creative economy, and human resource development (HR) to develop tourism in Bensamar Kampung Tuha. The method used in this research is factor analysis using a quantitative approach. The sampling technique is random, with a total of 40 respondents. The results of factor analysis show that local wisdom is the most important variable for the success of Bensamar Kampung Tuha's tourism development strategy. The results show that tourism development strategies that focus on local wisdom can increase destination attractiveness, strengthen local communities, and ensure environmental and cultural sustainability. This study suggests that tourism development in Bensamar Kampung Tuha should focus on strengthening local wisdom, while still considering the importance of environmental protection, historical and cultural revival, creative economy, and human resource development.